1997
DOI: 10.1089/hum.1997.8.15-1785
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Biologically Active Human Insulin-like Growth Factor-I Following Intramuscular Injection of a Formulated Plasmid in Rats

Abstract: Recent evidence has shown that insulin-like growth factor-I (IGF-I) plays an important role in the development, maintenance, and regeneration of peripheral nerves and skeletal muscle. IGF-I offers the potential to treat neuromuscular diseases in humans. We have developed a nonviral gene therapy method to express and produce localized and sustained therapeutic levels of IGF-I within target muscles by intramuscular injection of formulated plasmids. The purpose of the present study was to demonstrate that intramu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…Treated animals were killed 1 week after the experiments as peak levels of transgene expression in muscle were usually found between 1 and 2 weeks. 18,19 Muscles were removed and sections were cut at intervals of 100 mm. The number of GFP-positive fibres was counted.…”
Section: Resultsmentioning
confidence: 99%
“…Treated animals were killed 1 week after the experiments as peak levels of transgene expression in muscle were usually found between 1 and 2 weeks. 18,19 Muscles were removed and sections were cut at intervals of 100 mm. The number of GFP-positive fibres was counted.…”
Section: Resultsmentioning
confidence: 99%
“…27 Recently, intra-muscular expression of biologically active human IGF-I and factor IX have also been demonstrated in vivo using this system. 28,29 To assess the immunogenicity of plasmid formulated in PINC, we assayed for the presence of anti-plasmid antibodies in serum of dogs repeatedly injected with this formulation and did not detect any antibodies to the administered plasmid (unpublished data). Furthermore, we observed that delivery of our expression system for IL-12 lacks any obvious toxicity such as loss of weight or any signs of distress, that has been reported in mice following systemic delivery of IL-12 protein.…”
Section: Discussionmentioning
confidence: 99%
“…27 This system has been used to obtain significant biological activity of a variety of transgene products. 28,29 Using this system to deliver IL-12 into two tumor models -immunogenic (Renca) and less immunogenic (CT26) -we show that up to 50% of tumorbearing mice in both models reject their tumors with the help of a primarily CD8 + T cell-mediated immune response that has long lasting memory.…”
Section: Correspondence: F Periclementioning
confidence: 99%
“…These levels of hIGF-I protein production by the L6 cell line infected with the hIGF-I/SeV were over 100-fold higher than those reported for the C2C12 cell line tranfected with a naked plasmid. 18 (3) The L6 cell line is known to not express IGF-I but present IGF-I receptor. 19 Therefore, the cell line is responsive to an exogenous IGF-I, thus resulting in the induction of hypertrophy.…”
Section: Resultsmentioning
confidence: 99%